The relationship of muscle oxygen saturation analyzer with other monitoring and quantification tools in a maximal incremental treadmill test - Osmani, Florent; Lago-Fuentes, Carlos; Alemany-Iturriaga, Josep; Barcala-Furelos, Martín (Frontiers in Physiology, 2023)
Introduction: The study aims to explore whether NIRS derived data can be used to identify the second ventilatory threshold (VT2) during a maximal incremental treadmill test in non-professional runners and to determine if there is a correlation between SmO2 and other valid and reliable exercise performance assessment measures or parameters for maximal incremental test. Methods: 24 participants were recruited for the study (5 women and 19 men). The devices used consisted of the following: i) a muscle oxygen saturation analyzer placed on the vastus lateralis of the right leg, ii) the Stryd power meter for running, iii) the Polar H7 heart rate band; and iv) the lactate analyzer. In addition, a subjective perceived exertion scale (RPE 1-10) was used. All of the previously mentioned devices were used in a maximal incremental treadmill test, which began at a speed of 8 km/h with a 1% slope and a speed increase of 1.2 km/h every 3 minutes. This was followed by a 30-second break to collect the lactate data between each 3-minute stage. Spearman correlation was carried out and the level of significance was set at p < 0.05. Results: The VT2 was observed at 87,41 ± 6,47 % of the maximal aerobic speed (MAS) of each participant. No relationship between lactate data and SmO2 values (p = 0.076; r = -0.156) at the VT2 were found. No significant correlations were found between the SmO2 variables and the other variables (p > 0.05), but a high level of significance and strong correlations were found between all the following variables: power data (W), heart rate (HR), lactate concentration (LT) and RPE (p < 0.05; r > 0.5). Discussion: SmO2 data alone were not enough to determine the VT2, and there were no significant correlations between SmO2 and the other studied variables during the maximal incremental treadmill test. Only 8 subjects had a breakpoint at the VT2 determined by lactate data. Conclusion: The NIRS tool, Humon Hex, does not seem to be useful in determining VT2 and it does not correlate with the other variables in a maximal incremental treadmill test